2016
DOI: 10.1007/s00586-016-4616-z
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal malalignment has a significant association with postoperative leg pain in adult spinal deformity patients

Abstract: Leg pain in patients with ASD was significantly associated with sagittal malalignment especially after surgical treatments. As these patients lose flexibility in the fused spinal segment, they can only depend on the remaining compensatory mechanisms below the pelvis (e.g., the hips and knees) to maintain a balanced posture. This may lead to a predisposition of these patients to postoperative leg symptoms related to spinal sagittal malalignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The prospective and long-term nature of the current study represent 2 important strengths. While many multicenter studies of ASD surgery exist from large, collaborative registries, 33 - 35 the majority of these studies are retrospective. Furthermore, the threshold for complex ASD surgery is defined differently throughout the literature, yet our current inclusion was fairly strict, evidenced by nearly 3 in 4 patients undergoing 3CO.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective and long-term nature of the current study represent 2 important strengths. While many multicenter studies of ASD surgery exist from large, collaborative registries, 33 - 35 the majority of these studies are retrospective. Furthermore, the threshold for complex ASD surgery is defined differently throughout the literature, yet our current inclusion was fairly strict, evidenced by nearly 3 in 4 patients undergoing 3CO.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that LL was less related to PT/PI or PT but more related to SS; the spine adjusted TK for the adaptation of pelvic changes. TK and PT were recognized as compensatory mechanisms in patients with ASD, and the cascade was also reported (26). In asymptomatic individuals, the thoracic spine has adequate compensatory capacity (27); thus, sagittal alignment could be maintained in those with a small PT/PI (subgroup 1), although they may have a higher risk of sagittal malalignment once the capacity for thoracic compensation is exhausted due to the pelvic retroversion being limited.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of sagittal vertebral alignment on the treatment of spinal disorders is of critical importance. The principles of sagittal balance are vital to achieve optimum outcomes when treating spinal disorders, since a failure to recognize malalignment in this plane can have significant consequences for the patient in terms of pain and deformity [27]. Normally, the spine is known to have a lordotic curves in the cervical and lumbar regions and a kyphotic curve in the thoracic region.…”
Section: Discussionmentioning
confidence: 99%